Combined therapy with dapagliflozin and entresto offers an additional benefit on improving the heart function in rat after ischemia-reperfusion injury - Sheung-Fat Ko; Pei Hsun Sung; Chih Chao Yang; John Y. Chiang; Hon Kan Yip (Biomedical Journal, 2023)
Background: This study tested whether combined dapagliflozin and entresto treatment would be superior to either one alone for preserving the left-ventricular ejection-fraction (LVEF) in rat after ischemia-reperfusion (IR) injury. Methods: Cell culture using H9C2 cells and IR injury in rat with dapagliflozin-entresto treatment were conducted in the present study. Results: In vitro flow-cytometric result showed that the intracellular and mitochondrial reactive oxygen species and mitochondrial permeability transition pore, and protein levels of oxidative-stress/DNA-damaged markers [NADPH-oxidase-1 (NOX-1)/NOX-2/oxidized-protein/γ-H2A-histone-family member X (γ-H2AX)] were significantly higher in hydrogen peroxide (H2O2) (300μM)-treated H9C2 cells as compared with the controls that were significantly reversed in sacubitril/valsartan and dapagliflozin therapy in the same H2O2-treated condition, whereas the protein expressions of antioxidants [Sirtuin-1 (SIRT1)/SIRT3/superoxide dismutase/catalase/glutathione peroxidase) exhibited an opposite pattern among the groups (all p<0.001). Adult-male-Sprague-Dawley rat (n=40) were equally categorized into group 1 (sham-operated control), group 2 (IR), group 3 (IR+dapagliflozin/20mg/kg/orally at 3h and post-days 1/2/3 after IR), group 4 (IR+entresto/100mg/kg/orally at 3h and post-days 1/2/3 after IR) and group 5 (IR+dapagliflozin+entresto) and the hearts were harvested by day 3 after IR. The 3rd day’s LVEF was highest in group 1, lowest in group 2 and significantly higher in group 5 than in groups 3/4, but it was similar between the latter two groups (p<0.001). The protein expressions of oxidative-stress (NOX-1/NOX-2/oxidized protein), fibrotic (transforming-growth factor-ß/phosphorylated-Smad3), apoptotic [mitochondrial-Bax/cleaved-caspase-3/cleaved-poly (ADP-ribose) polymerase], mitochondria/DNA damaged (cytosolic-cytochrome-c/γ-H2AX), pressure-overload/heart-failure [brain natriuretic peptide (BNP)/ß-myosin heavy chain] and autophagic (ratio of meiotic cyclins CLB3-II/CLB3-I) biomarkers, and the upstream (high-mobility group box 1/Toll-like receptor-4/MyD88/phosphorylated-nuclear factor-κB and downstream [interleukin (IL)-1ß/IL-6/tumor necrosis factor-α] inflammatory signalings revealed an antithetical features of LVEF among the groups (all p<0.0001). The cellular levels of inflammatory (myeloperoxidase+/CD68+), pressure-overload/heart-failure (BNP+) and DNA-damage (γ-H2AX+) biomarkers as well as infarct area demonstrated an opposite pattern of LVEF among the groups (all p<0.0001). Conclusion: Incorporated entresto-dapagliflozin treatment was superior to either one alone on protecting the heart against IR injury.